Government livelihood project - free influenza vaccination for the older population in China: the example of Zhejiang Province - Wang, Xiaoxiao; Jiang, Wei; Yu, Zhao; Jiang, Weiping; Zhu, Xiaowei; Wang, Zhen; Sun, Jimin; Zhang, Hangjie (Frontiers in Public Health, 2025)
Influenza vaccination is an effective measure to prevent and control influenza, and countries worldwide consider older people a key recommended population for influenza vaccination. From 2020, Zhejiang Province has provided free influenza vaccination to anyone aged ≥70 years as part of its livelihood projects. In certain counties, the program is also offered to those aged ≥60 years. This measure has made influenza vaccination more convenient and has advanced the strategy for acceptance of influenza vaccines and improved readiness for a pandemic. Furthermore, it serves as an example for other Chinese provinces looking to implement free influenza vaccination programs.